2011
DOI: 10.1016/j.scitotenv.2011.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Noise measurements as proxies for traffic parameters in monitoring networks

Abstract: SummaryDue to their typically high traffic intensity, urban ring roads are characterized by high noise levels and high concentrations of airborne pollutants. Hence, such locations are often priority measurement locations in monitoring networks. Unfortunately, the high purchase and operational cost of most airborne pollutant sensors severely limits the number of such sensors that can be deployed, leading to a (too) limited spatial resolution. The present research describes how low cost microphones could be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The speed estimation problem has been also extensively addressed, e.g., in [11]- [16]. A recent trend consists in considering the pass-by noise as a measure of the energy consumption; in 2011, Can et al successfully showed the correlation between emitted airborne pollutant and road traffic noise near a highway [17]. This is a brief overview of what information traffic noise can provide.…”
Section: Introductionmentioning
confidence: 99%
“…The speed estimation problem has been also extensively addressed, e.g., in [11]- [16]. A recent trend consists in considering the pass-by noise as a measure of the energy consumption; in 2011, Can et al successfully showed the correlation between emitted airborne pollutant and road traffic noise near a highway [17]. This is a brief overview of what information traffic noise can provide.…”
Section: Introductionmentioning
confidence: 99%
“…A key constraint in the development and refinement of such models is the difficulty in capturing noise frequencies that are representative of traffic sources, rather than reliance on the conventional Aweighted SPL, dBA for model construction. In a recent Belgian study (Can, Dekoninck, et al, 2011) engine noise and its corresponding low frequencies (around 100 Hz) were found to predominate at both ends of the speed spectrum: -at low speeds and during accelerations, with rolling noise containing many medium frequencies (around 1 kHz), dominant for vehicles speeds exceeding 50-70 kph (op. cit.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive models have been developed to estimate measured total particle number (TPN) adjusted for meteorological conditions for specific noise indicators (L2KHz -L125Hz = low to med frequency noise bands (Can, Rademaker, et al, 2011). These models have shown strong correlation (Spearman 0.62) between measured and predicted TPN based on wind speed and wind direction.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 depicts the ranking for the features (by backward searching method and based on the inter-intra criterion) originally introduced in the texture and noise correlation study. [15][16][17] The procedure of ranking the features is important to select the most valuable features in order to derease the computational load of the classification/identification process. These features are shown in Table 2.…”
Section: Pavement Featuresmentioning
confidence: 99%